A green approach to the synthesis of novel phytosphingolipidyl β-cyclodextrin designed to interact with membranes - Miao, Yong; Djedaïni-Pilard, Florence; Bonnet, Véronique (Beilstein Journal of Organic Chemistry, 2014)
This work reports the synthesis of a new family of mono-substituted amphiphilic cyclodextrins using a green methodology. Reactions using greener and safer catalysts with more environmentally friendly purification solvents were performed. Four unreported mono-substituted cyclodextrins bearing a phytosphingolipidyl chain and a fatty acid chain (C10, C12, C14 and C18) were successfully obtained with a promising yield.
Keywords: fatty ester; green chemistry; lipase; mono-substituted amphiphilic cyclodextrins; peptide Coupling; solvent-free medium; transesterification

Cyclodextrins and their complexes - Dodziuk, H. (Wiley-VCH, 2006)

(untitled) - Paolino, D.; Cosco, D.; Molinaro, R.; Celia, C.; Fresta, M. (Drug Discovery Today, 2011)

(untitled) - Gervaise, C.; Bonnet, V.; Wattraint, O.; Aubry, F.; Sarazin, C.; Jaffrès, P.-A.; Djedaïni-Pilard, F. (Biochimie, 2012)

(untitled) - Liu, X.; Testa, B.; Fahr, A. (Pharm. Res., 2011)

(untitled) - Silva, O. F.; Fernández, M. A.; Pennie, S. L.; Gil, R. R.; de Rossi, R. H. (Langmuir, 2008)

(untitled) - Auzély-Velty, R.; Djedaïni-Pilard, F.; Désert, S.; Perly, B.; Zemb, T. (Langmuir, 2000)

(untitled) - Moutard, S.; Perly, B.; Godé, P.; Demailly, G.; Djedaïni-Pilard, F. (J. Inclusion Phenom. Macrocyclic Chem., 2002)

(untitled) - Bonnet, V.; Favrelle, A.; Aubry, F.; Sarazin, C.; Djedaïni-Pilard, F. (J. Inclusion Phenom. Macrocyclic Chem., 2013)

(untitled) - Gervaise, C.; Bonnet, V.; Sarazin, C.; Djedaïni-Pilard, F. (New J. Chem., 2012)

(untitled) - Liu, Z.-T.; Shen, L.-H.; Liu, Z.-W.; Lu, J. (J. Mater. Sci., 2009)

(untitled) - Miao, Y.; Rousseau, C.; Mortreaux, A.; Martin, P.; Zinck, P. (Polymer, 2011)

(untitled) - El-Faham, A.; Funosas, R. S.; Prohens, R.; Albericio, F. (Chem. – Eur. J., 2009)

(untitled) - Favrelle, A.; Bonnet, V.; Sarazin, C.; Djedaïni-Pilard, F. (J. Inclusion Phenom. Macrocyclic Chem., 2007)

(untitled) - Favrelle, A.; Bonnet, V.; Avondo, C.; Aubry, F.; Djedaïni-Pilard, F.; Sarazin, C. (J. Mol. Catal. B: Enzym., 2010)